Structural Explanation to the Establishment of the Truth and Reconciliation Commissions: A Comparative Study of Five Countries - Sari, Angguntari Ceria (Parahyangan Center for International Studies, 2025)
Why has Indonesia, a former military dictatorial regime, only commissioned the official Truth and Reconciliation Commissions (TRC) later than South Africa, Brazil, Uruguay, Chile, and South Korea? This article compares how the six democratic governments in Africa, Latin America, and East Asia deal with human rights violations committed by officials of previous authoritarian regimes. I posit a structural explanation for the variation in the establishment of a TRC in former authoritarian countries that underwent pacted transition or authoritarian-initiated transition. Using a qualitative approach, I argue that a combination of the level of external and internal security threats facing the country, and the military tary doctrine which is adopted by the military determines the timing of the establishment of a TRC. Understanding the timing of the establishment of the TRC is important as victims and their relatives need closure over past human rights violations and the delay in the establishment of it can increase distrust to the government. Keywords: Indonesia, Truth and Reconciliation Commissions, Civil-Military, Transitional Justice, Democratization, Military-Civilian Relations